Perceived benefits, constraints and determinants of sustainable intensification of mixed crop and livestock systems in the Sahelian zone of Burkina Faso - Ayantunde, Augustine A.; Oluwatosin, B.O.; Yameogo, Viviane; Wijk, Mark T. van (Informa UK Limited, 2020)
In West African Sahel, there has been an only limited intensification of the mixed crop and livestock systems due to many constraints faced by smallholder farmers including climate change, low use of external inputs, insecure land tenure, and low adoption of productivity-enhancing technologies. However, the growing demand for food caused by a rapidly growing population offers opportunities for intensification of farming systems in the region in view of the current low productivity. A study involving 400 households was carried out in two provinces (Seno and Yatenga) in Burkina Faso in the Sahelian zone of the country to characterize the intensification practices by smallholder farmers in mixed crop and livestock systems. Our results confirmed the advantage of intensification practices in terms of increased crop and livestock productivity which is critical to improving food security. Also, the results showed that access to extension services is an important determinant of adoption of intensification practices in both study sites, which reaffirmed the vital role of extension services in adoption of agricultural technologies. The results also showed strong differences in adoption of intensification practices between the two provinces driven by their divergent history of land use, even though both provinces fall in the same agro-ecological zone.